2016
DOI: 10.1002/jms.3838
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and untargeted profiling of alkaloids in herbal extracts using online solid‐phase extraction and high‐resolution mass spectrometry (Q‐Orbitrap)

Abstract: The biological activity of alkaloids (ALKs) and the different content of these natural products in herbs and plants have made them an attractive field for chemical studies. A screening method automatically combining online solid-phase purification and concentration of samples with analysis using ultra-high performance liquid chromatography coupled with a hybrid quadrupole orbitrap mass spectrometer was developed and is reported in this paper. The proposed quantification method was validated for 35 ALKs with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…In the previous work proposed by Nardin et al, the RT and fragmentation of 48 alks was confirmed by analysing extracts of Datura stramonium and Hyoscyamus niger for 4 Trp alks, Solanum nigrum for 1 Gst alk, Lobelia inflata for 23 Ppr‐type alks, Senecio vulgaris for 10 Pyz alks, Arnica montana for 1 pyrrolidine (Pyl) alk, Gelsemium sempervirens for 8 Ind alks, and Ranunculus montanus for 1 Qnl‐type alk.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…In the previous work proposed by Nardin et al, the RT and fragmentation of 48 alks was confirmed by analysing extracts of Datura stramonium and Hyoscyamus niger for 4 Trp alks, Solanum nigrum for 1 Gst alk, Lobelia inflata for 23 Ppr‐type alks, Senecio vulgaris for 10 Pyz alks, Arnica montana for 1 pyrrolidine (Pyl) alk, Gelsemium sempervirens for 8 Ind alks, and Ranunculus montanus for 1 Qnl‐type alk.…”
Section: Resultsmentioning
confidence: 63%
“…Chromatographic separation was obtained using a Thermo Ultimate R3000 UHPLC (Thermo Scientific, Sunnyvale, CA, USA), furnished with a Rheodyne 6‐port automated switching valve and a pump module that allowed control of two independent fluid systems. The method used the same approach proposed by Nardin et al…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations